2004
DOI: 10.1128/jb.186.6.1658-1666.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Legionella pneumophila PilT Homologue DotB Exhibits ATPase Activity That Is Critical for Intracellular Growth

Abstract: The ability of Legionella pneumophila to grow and cause disease in the host is completely dependent on a type IV secretion system known as the Dot/Icm complex. This membrane-spanning apparatus translocates effector molecules into host cells in a process that is poorly understood but that is known to require the putative ATPase DotB. One possible role for DotB is suggested by its similarity to the PilT family of proteins, which mediate pilus retraction. To better understand the molecular behavior of DotB, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
86
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 43 publications
5
86
0
3
Order By: Relevance
“…More data supporting this assumption have been reported: upon lipid binding, VirB11 is seen to undergo conformational changes (Krause et al, 2000b) and the same eVect is also observed for nucleotide binding (Savvides et al, 2003). Moreover, a functional nucleotide binding site is required for localization of VirB11 to the membrane (Sexton et al, 2004). This may be the reason why nucleotide binding motif (Walker A) mutations of VirB11 fail to transfer the T-DNA substrate to the channel components VirB6 and VirB8, as detected by TrIP analysis in A. tumefaciens (Atmakuri et al, 2004).…”
Section: Virb11: a Ring-shaped Cytoplasmic Ntpase Fuelling The Secretmentioning
confidence: 68%
See 1 more Smart Citation
“…More data supporting this assumption have been reported: upon lipid binding, VirB11 is seen to undergo conformational changes (Krause et al, 2000b) and the same eVect is also observed for nucleotide binding (Savvides et al, 2003). Moreover, a functional nucleotide binding site is required for localization of VirB11 to the membrane (Sexton et al, 2004). This may be the reason why nucleotide binding motif (Walker A) mutations of VirB11 fail to transfer the T-DNA substrate to the channel components VirB6 and VirB8, as detected by TrIP analysis in A. tumefaciens (Atmakuri et al, 2004).…”
Section: Virb11: a Ring-shaped Cytoplasmic Ntpase Fuelling The Secretmentioning
confidence: 68%
“…Along with VirB4 and the CP (VirD4), VirB11 is thought to energize the type IV secretion machinery either for complex assembly, pilus production and/or substrate secretion. The NTPase activity of several VirB11-like proteins has been determined in vitro (Christie et al, 1989;Krause et al, 2000b;Rivas et al, 1997;Sexton et al, 2004), revealing a rather weak activity similar to the one observed for chaperons like DnaK (Zylicz et al, 1983). VirB11 of A. tumefaciens has been reported to additionally possess an autophosphorylation activity (Christie et al, 1989), however, such an activity was not detected for any other member of the family of VirB11-like proteins.…”
Section: Virb11: a Ring-shaped Cytoplasmic Ntpase Fuelling The Secretmentioning
confidence: 94%
“…pneumophila 52 , bearing either the vector pJB1625 53 or the Tet(56) complementing clone pJB7207. Minimum inhibitory concentrations were determined according to Clinical and Laboratory Standards Institute (CLSI) procedures with the following modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pJB955 contains a 3.2-kb HincII/EcoRI fragment of DNA adjacent to the dot/icm region II cloned into the HincII/EcoRI sites of pBluescript II KS ϩ . Natural competence reporter constructs pJB957, pJB964, and pJB1389 are pJB955 derivatives with Kan r , Cm r , or Gent r cassettes The cloning vector pJB1653, used to create proQ and comR complementing clones, is a Gent r derivative of the RSF1010 cloning vector pJB908 (43). First, the pJB908 polylinker HindIII site was replaced with a NotI site, creating plasmid pJB1301.…”
Section: Methodsmentioning
confidence: 99%